Advertisements
Advertisements
Question
If cos (α + β) = 0, then sin (α – β) can be reduced to ______.
Options
cos β
cos 2β
sin α
sin 2α
Solution
If cos (α + β) = 0, then sin (α – β) can be reduced to cos 2β.
Explanation:
According to the question,
cos(α + β) = 0
Since, cos 90° = 0
We can write,
cos(α + β) = cos 90°
By comparing cosine equation on L.H.S and R.H.S,
We get,
(α + β) = 90°
α = 90° – β
Now we need to reduce sin(α – β),
So, we take,
sin(α – β) = sin(90° – β – β) = sin(90° – 2β)
sin(90° – θ) = cos θ
So, sin(90° – 2β) = cos 2β
Therefore, sin(α – β) = cos 2β
APPEARS IN
RELATED QUESTIONS
Prove the following identities, where the angles involved are acute angles for which the expressions are defined:
`(cos A-sinA+1)/(cosA+sinA-1)=cosecA+cotA ` using the identity cosec2 A = 1 cot2 A.
Without using trigonometric tables evaluate
`(sin 35^@ cos 55^@ + cos 35^@ sin 55^@)/(cosec^2 10^@ - tan^2 80^@)`
Prove the following identities:
cosec4 A – cosec2 A = cot4 A + cot2 A
Prove the following identities:
`sqrt((1 + sinA)/(1 - sinA)) = sec A + tan A`
If `cosA/cosB = m` and `cosA/sinB = n`, show that : (m2 + n2) cos2 B = n2.
If 2 sin A – 1 = 0, show that: sin 3A = 3 sin A – 4 sin3 A
Prove that:
(tan A + cot A) (cosec A – sin A) (sec A – cos A) = 1
`1/((1+ sintheta ))+1/((1- sin theta ))= 2 sec^2 theta`
`(1+ tan theta + cot theta )(sintheta - cos theta) = ((sec theta)/ (cosec^2 theta)-( cosec theta)/(sec^2 theta))`
If ` cot A= 4/3 and (A+ B) = 90° ` ,what is the value of tan B?
Find the value of ` ( sin 50°)/(cos 40°)+ (cosec 40°)/(sec 50°) - 4 cos 50° cosec 40 °`
If `sin theta = x , " write the value of cot "theta .`
If \[\cos A = \frac{7}{25}\] find the value of tan A + cot A.
If cos (\[\alpha + \beta\]= 0 , then sin \[\left( \alpha - \beta \right)\] can be reduced to
Prove the following identity :
`(cotA + tanB)/(cotB + tanA) = cotAtanB`
Prove the following identity :
`(secθ - tanθ)^2 = (1 - sinθ)/(1 + sinθ)`
Prove that `(tan θ + sin θ)/(tan θ - sin θ) = (sec θ + 1)/(sec θ - 1)`
Choose the correct alternative:
sec2θ – tan2θ =?
The value of the expression [cosec(75° + θ) – sec(15° – θ) – tan(55° + θ) + cot(35° – θ)] is ______.
Let x1, x2, x3 be the solutions of `tan^-1((2x + 1)/(x + 1)) + tan^-1((2x - 1)/(x - 1))` = 2tan–1(x + 1) where x1 < x2 < x3 then 2x1 + x2 + x32 is equal to ______.